Restricționarea unor drepturi ale cetățenilor în perioada stării de urgență - Slusarenco, Svetlana (Tipografia Artpoligraf, 2021)
The Parliament of the Republic of Moldova has the power to declare a state of emergency, siege and war. During a state of emergency, siege or war, depending on the gravity of the situation which led to its establishment, may be restricted, if necessary, to the exercise of the rights or freedoms of citizens in accordance with article 54 of the Constitution. With regard to the restriction of certain rights, the principle of proportionality must be taken into account, according to which any measure taken must be appropriate, necessary and proportionate.
RESTRICTION OF CITIZENS ‚RIGHTS DURING THE EMERGENCY PERIOD
Keywords: state of emergency; rights; restrictions; fleuibility; proportionality; pandemic